2022
DOI: 10.3390/genes13122331
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Identifying Key Genes Involved in HBV-Related Hepatocellular Carcinoma for Primary Care Surveillance of Patients with Cirrhosis

Abstract: Cirrhosis is frequently the final stage of disease preceding the development of hepatocellular carcinoma (HCC) and is one of the risk factors for HCC. Preventive surveillance for early HCC in patients with cirrhosis is advantageous for achieving early HCC prevention and diagnosis, thereby enhancing patient prognosis and reducing mortality. However, there is no highly sensitive diagnostic marker for the clinical surveillance of HCC in patients with cirrhosis, which significantly restricts its use in primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, the exact mechanism by which HBV affects CDK1 expression and leads to HCC progression is still not fully understood and requires further studies. Moreover, it has been suggested that CDK1 is a predictive biomarker in HBV‐related HCC, and its overexpression is associated with a negative prognosis and the advancement of tumors 31 . Increased levels of CDK1 expression are linked to more advanced tumor grades and stages, suggesting its role in promoting cancer aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism by which HBV affects CDK1 expression and leads to HCC progression is still not fully understood and requires further studies. Moreover, it has been suggested that CDK1 is a predictive biomarker in HBV‐related HCC, and its overexpression is associated with a negative prognosis and the advancement of tumors 31 . Increased levels of CDK1 expression are linked to more advanced tumor grades and stages, suggesting its role in promoting cancer aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained GSE36376 cohort (193 HCC and 240 adjacent normal tissues), GSE14520 cohort (247 HCC and 241 adjacent normal tissues), GSE25097 cohort (268 HCC and 243 adjacent normal tissues) and GSE10143 cohort (80 HCC tissues) from GEO. LIRI cohort (273 HCC and 203 adjacent normal tissues), the last external cohort, was obtained from the ICGC ( Liu et al, 2019 ; Yang et al, 2021b ; Jin et al, 2022 ; Li et al, 2022 ). ImmPort ( immport.org/home ) and InnateDB ( innatedb.ca/ ) databases provided 2,660 immune-related genes (IRGs), while FerrDb ( zhounan.org/ferrdb ) database shared 259 ferroptosis-related genes (FRGs) for us.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, CDKN3, which influences the cell cycle and is intimately connected to the occurrence and progression of HCC, was paramount hum gene in promoting HBV induced hepatic cancer. 24 SET and MYND domain containing 3 (SMYD3), zymogen granule protein 16 (ZG16), family with sequence similarity 110 member C (FAM110C), and cytochrome P450 family 26 subfamily a member 1 (CYP26A1) are distinct genes to distinguish HBV infection and HBVinduced HCC and are anticipated to be novel targets for the occurrence of HBV-associated HCC and prognostic evaluation. 25 2 of 9 -ADUGNA…”
Section: Genomicsmentioning
confidence: 99%
“…In order for liver cirrhosis to progress into HCC, three critical genes such as cyclin‐dependent kinase inhibitor 3 (CDKN3), Cytochrome P450 family 2 subfamily C member 9 (CYP2C9), and Lecithin‐Cholesterol Acyltransferase were appear to be crucial. Of these, CDKN3, which influences the cell cycle and is intimately connected to the occurrence and progression of HCC, was paramount hum gene in promoting HBV induced hepatic cancer 24 . SET and MYND domain containing 3 (SMYD3), zymogen granule protein 16 (ZG16), family with sequence similarity 110 member C (FAM110C), and cytochrome P450 family 26 subfamily a member 1 (CYP26A1) are distinct genes to distinguish HBV infection and HBV‐induced HCC and are anticipated to be novel targets for the occurrence of HBV‐associated HCC and prognostic evaluation 25 …”
Section: Histomolecular Characterisation Of Hbv Induced Liver Cancermentioning
confidence: 99%